The Degree of Involving Seventh Grade Students in the Content of the English Language Textbook in Jordan - Al-Amayreh, Rami Mousa; Zaghlool, Zuhair Dawood (Journal of Curriculum and Teaching Methodology, 2023)
The aim of this study is to determine the degree of involvement of the English textbook for seventh grade students in Jordan, which includes the student's book and the exercise book, by presenting the text, activities and questions. In their first and second parts, the data were collected according to the paragraphs of Romey, and the arithmetic mean, frequency, and percentages were calculated. The results show, according to the Romey coefficient, that the inclusion of the text was acceptable, and its values were in the student’s book and the exercise book, respectively (0.86, 0.88). The results also show that the students' participation in the questions in the student's book and the exercise book, respectively, was (0.56, 0.68). According to the involvement through activities, it was acceptable in the student's book and reached (1.23). As for the exercise book, its participation coefficient was (2.27), because the exercise book consists entirely of questions as a simultaneous application with the lessons in the student's book. Finally, the study recommends that more analytical studies that should be conducted on English books in other classrooms.
Keywords: The degree of student involvement; English subject; Seventh grade students